BASIC CONCEPT FOR USING INTERACTIVE VISUAL-BASED LEARNING TO STUDENTS WITH AUTISM - Siti Sopiah; Edi Purnama (Jurnal Sastra - Studi Ilmiah Sastra, 2025)
The aim of this paper is to know and apply the using interactive visual based learning to students with autism in the area of inclusive elementary school.  Using interactive visual based learning is important at the area of inclusive school and university. This paper uses multiple theories related with characteristics of Autism. This paper is a library based descriptive study. The sourced has been taken from website, any source from journals and e books. The sources are read, selected, analyzed and concluded. It concludes that the This study highlights key principles such as visual learning strengths, structured routines, multimodal engagement, and minimized language load. The goal is to support the development of practical and inclusive English learning media tailored for students with autism in inclusive classrooms.